NUTQ O`STIRISH MASHG`ULOTLARINI INTERFAOL USULLAR VOSITASIDA TASHKIL ETISH: NUTQ O`STIRISH MASHG`ULOTLARINI INTERFAOL USULLAR VOSITASIDA TASHKIL ETISH - Boyqulova, Maftuna (Maktabgacha taʼlim jurnali, 2021)
NUTQ O`STIRISH MASHG`ULOTLARINI INTERFAOL USULLAR VOSITASIDA TASHKIL ETISH